Public Perception of Vocational Education - Kasim, E S; Fachriah, T (KnE Social Sciences, 2018)
Public perception of vocational education aims to provide a research-based assessment of vocational education. The research method used is a quantitative approach with data collection techniques through questionnaires and literature study. The analytical method used is univariate analysis. The results showed that the perception of the community—in this case, the perception of parents/students of grade 3 SMAN 2 Cibinong—about vocational education is good. The perception of students of the vocational program (diploma) is good. And the perception of Human Resources Manager/Supervisor of the organizations where the Vocational UI Program students completed their apprenticeship is also good. Keywords: vocational education, public perception